Redesign of Ciamis Station With an Industrialist Concept Approach Using Autodesk Revit Application - ASHARI, MOCHAMMAD ILHAM; Aghastya, Adya; Adi, Wahyu (Nusantara Publisher, 2024)
Ciamis Station is one of the train stations located on the Bandung-Banjar railway route. This station needs facility improvement to meet the standard of a medium-class rail station. The purpose of this research is to identify the existing conditions of Ciamis Station, determine the class of Ciamis Station according to PM 33 of 2011, analyze the compliance of station standards according to PM 29 of 2011, redesign the station, and calculate the quantity of work with industrialist concept approach. Field survey data is used as primary data in the study. Passenger volume and existing floor plan are secondary data used in the analysis. Ciamis Station redesign planning is carried out to improve and develop Ciamis Station to increase the facilities using the Autodesk Revit application. Output results are in the form of layout, 3-dimensional views, and interiors of rooms, according to PM 63 of 2019 and the Railway Station Standardization Book. The result of the floor area for constructing the Ciamis Station room is 1.178 m2. The industrialist design concept uses materials, color, interior, and exposure of the station building. The result also shows the estimation of quantities for the construction process.